Reassembling Scholarly Communications Histories, Infrastructures, and Global Politics of Open Access - Eve, Martin Paul; Gray, Jonathan (The MIT Press, 2020)
A critical inquiry into the politics, practices, and infrastructures of open access and the reconfiguration of scholarly communication in digital societies. The Open Access Movement proposes to remove price and permission barriers for accessing peer-reviewed research work-to use the power of the internet to duplicate material at an infinitesimal cost-per-copy. In this volume, contributors show that open access does not exist in a technological or policy vacuum; there are complex social, political, cultural, philosophical, and economic implications for opening research through digital technologies. The contributors examine open access from the perspectives of colonial legacies, knowledge frameworks, publics and politics, archives and digital preservation, infrastructures and platforms, and global communities. The contributors consider such topics as the perpetuation of colonial-era inequalities in research production and promulgation; the historical evolution of peer review; the problematic histories and discriminatory politics that shape our choices of what materials to preserve; the idea of scholarship as data; and resistance to the commercialization of platforms. Case studies report on such initiatives as the Making and Knowing Project, which created an openly accessible critical digital edition of a sixteenth-century French manuscript, the role of formats in Bruno Latour's An Inquiry into Modes of Existence, and the Scientific Electronic Library Online (SciELO), a network of more than 1,200 journals from sixteen countries. Taken together, the contributions represent a substantive critical engagement with the politics, practices, infrastructures, and imaginaries of open access, suggesting alternative trajectories, values, and possible futures.